PTPN21 inhibits cell apoptosis of acute lymphoblastic leukemia induced by chemotherapeutic agents via GADD45A and JNK signaling pathway - Chenze Zhao; Yu Zhang; Linlin Huang; Jingjing Xiang; Baodong Ye; Ni Zhu (PLoS ONE, 2025)
Acute lymphoblastic leukemia (ALL), a hematologic malignancy characterized by the uncontrolled proliferation of immature lymphocytes, often results in unfavorable long-term survival prospects for patients. PTPN21, a protein with established roles in oncogenesis, has been implicated in the pathogenesis of ALL. This study explores the role of PTPN21 in ALL cell apoptosis induced by chemotherapeutic agents. Key findings reveal that elevated PTPN21 levels hinder the apoptosis of ALL cells in response to vincristine (VCR) and daunorubicin (DNR). PTPN21 accomplishes this by inhibiting the GADD45A and JNK signaling pathways, thereby reversing cell cycle arrest in the G2/M phase. Restoring GADD45A reverses the anti-apoptotic effect of PTPN21. These findings suggest that targeting PTPN21 in conjunction with chemotherapy may represent a novel therapeutic strategy for ALL, offering potential implications for improving treatment efficacy and overcoming drug resistance.